Ethical issues of surrogacy - Seidinova, M.A. (Bulletin of the Karaganda University “Law Series”, 2023)
The global market for commercial surrogacy is growing at a significant pace. Every year, thousands of women agree, for a fee, to bear a child for another woman. As a result, thousands of children are born conceived by one woman, but claimed by another. The central argument of this article is that surrogacy should be approached as a complex commercial, ethical, legal relationship. At the moment, there is an active international trade in uterus, sperm and eggs. There are rapidly advancing medical technologies that have undoubtedly increased both the demand for surrogacy services and the supply from surrogate mothers. But the fundamentals of the market rule governing surrogate motherhood, norms, laws are developing much more slowly. Some states, such as the USA, France, Germany, Austria regulate issues related to surrogacy mainly in the form of a ban; other states create the most liberal legislation, such as India, Russia, Kazakhstan. In the article, the author concluded that he divided the ethical and moral issues of surrogacy into two camps of all countries in the world: supporters and opponents who compare it with the slavery of women. The necessity of establishing security measures to ensure that there will be no exploitation of women in a difficult financial situation in this transaction is justified.